A Strong Relationship Between Oral Squamous Cell Carcinoma and DNA Repair Genes - Avci, Hakan; Ergen, Arzu; Bireller, Elif Sinem; Ertugrul, Baris; Cakmakoglu, Bedia (Biochemical genetics, 2017)
Single nucleotide polymorphisms of DNA repair genes alter protein function and modulate DNA repair efficiency in various cancers. The X-ray repair cross-complementing group (XRCC) is responsible for the repair of DNA base damage and single-strand breaks. The aim of our study was to investigate the association of XRCC1 Arg399Gln and XRCC3 Thr241Met polymorphisms with the susceptibility to develop oral squamous cell carcinoma (OSCC) in Turkish subjects. One hundred eleven patients with OSCC and 148 healthy controls were recruited for the study. Genetic analysis was performed using polymerase chain reaction/restriction fragment length polymorphism (PCR/RFLP). We found that the XRCC1 Arg399Gln Gln/Gln genotype and Gln allele were risk factors for OSCC. Also, Arg/Arg genotype and Arg allele had protective effects against OSCC. Relative to XRCC3 Thr241Met polymorphism, carrying homozygote variants (Thr/Thr and Met/Met) was related with elevated OSCC risk. However, the heterozygote genotype and Thr allele variants were shown to be protective against OSCC. We suggest that XRCC1 Arg399Gln Gln/Gln genotype, Gln allele, and homozygote variants of XRCC3 Thr241Met polymorphism may be a risk factor for predisposition of OSCC in Turkish. In addition, XRCC3 Thr241Met genotype could be associated with tumor size and level of daily smoking.